Ecowomanism - Harris, Melanie L. (Worldviews, 2016)
This essay provides a definition and theoretical frame for ecowomanism. The approach to environmental justice centers the perspectives of women of African descent and reflects upon these women’s activist methods, religious practices, and theories on how to engage earth justice. As a part of the womanist tradition, methodologically ecowomanism features race, class, gender intersectional analysis to examine environmental injustice around the planet. Thus, it builds upon an environmental justice paradigm that also links social justice to environmental justice. Ecowomanism highlights the necessity for race-class-gender intersectional analysis when examining the logic of domination, and unjust public policies that result in environmental health disparities that historically disadvantage communities of color. As an aspect of third wave womanist religious thought, ecowomanism is also shaped by religious worldviews reflective of African cosmologies and uphold a moral imperative for earth justice. Noting the significance of African and Native American cosmologies that link divine, human and nature realms into an interconnected web of life, ecowomanism takes into account the religious practices and spiritual beliefs that are important tenets and points of inspiration for ecowomanist activism.